Impact evaluation of Batho-Pele Principles in delivery of housing services : a case study of CoGHSTA in Limpopo Province - Tjebana, Mamokgage, Papiki (My University, 2020)
The Low-cost housing delivery programme was launched at the dawn of democracy under the negotiated housing policy in year 1994 with the aim of addressing the backlog in housing provisioning. The programme was also meant to address the past injustices. The democratic government launched Batho Pele Principles in the year 1997 as a framework within which public services would be provided. The purpose of the study was to evaluate the impact of adherence to Batho Pele Principles in the provisioning of low-cost housing services by the Cooperative Governance Human Settlements and Traditional Affairs Department in Limpopo Province.The qualitative research methods were applied to generate data relevant for the study. The study involved the reviewing of secondary data available in the department in the form of Annual performance plans, Annual performance reports, Service delivery improvement plan, Service standards, Citizens’ report and minutes taken during departmental self-evaluation meetings. The findings reveal that CoGHSTA underperformed on delivery of low-cost houses targets for three consecutive years. The underperformance was attributed to protracted procurement of service providers and non-approval of application forms due to insufficient/irrelevant information provided by the applicants. Inadequate consultation and involvement of beneficiaries prior to and during the implementation of low-cost housing projects appeared to be a major issue of concern. The adherence to Batho Pele Principles was not adequately implemented. The study recommends that enhancement of housing consumer education will help a great deal in reducing the number of application forms with insufficient/irrelevant information being submitted for processing. The appointment of service providers during the year preceding the implementation year would provide ample time for planning.
Thesis (MPA.) -- University of Limpopo, 2020
Keywords: Housing delivery; Batho pele principles; Democratic government; Low-cost; Public services; Housing -- South Africa -- Limpopo